2011
DOI: 10.1111/j.1365-2664.2011.02009.x
|View full text |Cite
|
Sign up to set email alerts
|

Demographic processes limiting seedling recruitment in arid grassland restoration

Abstract: Summary 1.Seeding is an important management tool in aridland restoration, but seeded species often fail to establish. Previous research has largely focused on the technical aspects of seeding with little effort directed at identifying demographic processes driving recruitment failures. 2. In tilled plots, in each of 3 years, we estimated life stage transition probabilities for three species commonly used in sage steppe restoration. We also took similar measurements on seed sown by managers following four majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
264
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(286 citation statements)
references
References 58 publications
18
264
0
4
Order By: Relevance
“…Greater heat or water stress on seeded plants during key lifecycle phases (e.g., emergence, germination) likely impedes restoration efforts that could benefit sage-grouse habitat after wildfire. A study of seeded grass recruitment in the Great Basin found that seedling emergence (and likely environmental conditions) in March-May was the main barrier to recruitment, with springsummer drought adding to mortality, but at lower levels (James et al 2011). Sites within the Snake River Plain were an exception to the latitudinal trend we observed, but these locations were also typically low in elevation and total precipitation.…”
Section: Treatment and Environmental Predictors Of Meeting Guidelinesmentioning
confidence: 54%
“…Greater heat or water stress on seeded plants during key lifecycle phases (e.g., emergence, germination) likely impedes restoration efforts that could benefit sage-grouse habitat after wildfire. A study of seeded grass recruitment in the Great Basin found that seedling emergence (and likely environmental conditions) in March-May was the main barrier to recruitment, with springsummer drought adding to mortality, but at lower levels (James et al 2011). Sites within the Snake River Plain were an exception to the latitudinal trend we observed, but these locations were also typically low in elevation and total precipitation.…”
Section: Treatment and Environmental Predictors Of Meeting Guidelinesmentioning
confidence: 54%
“…However, in other areas and particularly for restoration at scale, the removal of barriers necessitates the efficient collection, handling and use of large volumes of viable seed. The development of the restoration seed bank concept, in conjunction with a systems approach, has highlighted the connected nature of processes ranging from seed procurement at scale, breaking of dormancy and emergence, to early establishment and subsequent maturation of the young plant at restoration sites (James et al 2011, Merritt and Dixon 2011, James et al 2013. Without considering all components of this chain of seed use, there remain impediments to increasing the likelihood of plant establishment in a cost-effective and predictable manner (James et al 2013).…”
Section: Restoring Species Composition Requires More Than Just Plantsmentioning
confidence: 99%
“…The four key life transitions that make up seedling recruitment are germination, seedling emergence, seedling establishment to an autotrophic state, and seedling survival through the end of the first growing season (Fenner and Thompson, 2005). Of these, emergence has been shown to be the most important for rangeland species ( James et al, 2011;Larson et al, 2014). Thus, native plant materials with an improved ability to emerge, particularly in unfavorable soil environments, may increase the probability of successful seedling recruitment.…”
Section: Improved Seedling Recruitmentmentioning
confidence: 99%